Radioprotective effects of Histamine H2 Receptor Antagonists on Gamma Rays Induced Human Peripheral Blood Lymphocytes - Narinder Kumar Sharma (Current Overview on Disease and Health Research Vol. 2, 2022)
The present study is conducted using metaphase chromosome for chromosome aberration and micronuclei analysis in order to examine the radioprotective effects of histamine H2 receptor antagonists on gamma rays induced clastogenic effects in vitro on human peripheral blood lymphocytes. Histamine H2 receptor antagonists are used to treat peptic ulcers in the clinic. Famotidine and Ranitidine were tested for their influence on 60Cobalt gamma-ray generated clastogenic effects using in vitro metaphase analysis and micronucleus assays. Six healthy participants provided heparinised whole blood, which was then gamma irradiated with 3Gy. In the present investigation, evaluation of radioprotective effects of Histamine H2 receptor antagonists is comprehensively investigated; Famotidine and Ranitidine on gamma-ray induced chromosome aberration and Micronuclei in vitro in human lymphocytes of six donors. Lymphocyte cultures were initiated and aqueous solution of Famotidine (150µg/ml) & Ranitidine (500µg/ml) was added at 0h and 24h. Cultures were harvested & processed at 48h & 72h for chromosome aberrations and micronucleus analysis respectively. At 0h & 24h after 3Gy gamma irradiation, cultures treated with Famotidine & Ranitidine independently showed significant decrease (p < 0.0001) in the frequency of chromosome aberration. At 0h & 24h Famotidine induced 60.91% & 56.42% inhibition in dicentrics & 59.39% & 56.21% inhibition was observed in total aberrations where as Ranitidine induce 52.11% & 43.54% inhibition in dicentrics and 53.06% & 46.66% inhibition in total aberrations at 0h & 24h. Significant decrease in the frequency of micronuclei was observed with Famotidine treatment after 3Gy of gamma irradiation, which induced inhibition of 48.83% (p < 0.0001) at 0hr & 5.02% (p < 0.016) at 24h. Reduction of the frequency of chromosomal aberrations in the lymphocytes treated with Famotidine and Ranitidine at 0h and 24h after irradiation with gamma ray (3Gy) indicate that drugs might reduce the clastogenic effect of radiation via radical scavenging mechanism and famotidine is more effective than the ranitidine – histamine H2 receptor antagonists studied. Radio protective effects of Histamine H2 receptor antagonists Famotidine and Ranitidine was observed on exposure to gamma-ray.